Randomized phase II clinical trial of ruxolitinib plus simvastatin in COVID19 clinical outcome and cytokine evolution - Garcia-Donas, Jesus; Martínez-Urbistondo, Diego; Velázquez Kennedy, Kyra; Villares, Paula; Barquin, Arántzazu; Dominguez, Andrea; Rodriguez-Moreno, Juan Francisco; Caro, Elena; Suarez del Villar, Rafael; Nistal-Villan, Estanislao; Yagüe, Monica; Ortiz, Maria; et al. (Frontiers in Immunology, 2023)
Background: Managing the inflammatory response to SARS-Cov-2 could prevent respiratory insufficiency. Cytokine profiles could identify cases at risk of severe disease. Methods: We designed a randomized phase II clinical trial to determine whether the combination of ruxolitinib plus simvastatin, could reduce the incidence of respiratory insufficiency in COVID-19. 48 cytokines were correlated with clinical outcome. Participants: Patients admitted due to COVID-19 infection with mild disease. Results: Up to 92 were included. Mean age was 64 ± 17, and 28 (30%) were female. 11 (22%) patients in the control arm and 6 (12%) in the experimental arm reached an OSCI grade of 5 or higher (p = 0.29). Unsupervised analysis of cytokines detected two clusters (CL-1 and CL-2). CL-1 presented a higher risk of clinical deterioration vs CL-2 (13 [33%] vs 2 [6%] cases, p = 0.009) and death (5 [11%] vs 0 cases, p = 0.059). Supervised Machine Learning (ML) analysis led to a model that predicted patient deterioration 48h before occurrence with a 85% accuracy. Conclusions: Ruxolitinib plus simvastatin did not impact the outcome of COVID-19. Cytokine profiling identified patients at risk of severe COVID-19 and predicted clinical deterioration.